2002
DOI: 10.1038/sj.jea.7500246
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Wertheimer–Leeper wire codes as a measure of exposure to residential magnetic fields over a 9- to 11-year interval

Abstract: The Wertheimer -Leeper ( W -L ) wire code is a construct used as a surrogate indicator of residential exposure to electromagnetic fields. However, little is known about how changes in electrical distribution systems affect wire code assignment. The wire code was determined for 150 homes in the Seattle, WA, area twice, 9 -11 years apart. For each home, the authors evaluated whether the electrical configuration around the home and the wire code changed between the two time points. The effect of wire code misclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another limitation is the use of wire codes as a surrogate for magnetic fields exposure since this surrogate is known to have limited ability to estimate magnetic field exposure and was used only in North American studies [29]. However, we used wire codes because our aim was to assess the role of selection bias and this approach could be applied to any known address without requiring active participation or property access.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the use of wire codes as a surrogate for magnetic fields exposure since this surrogate is known to have limited ability to estimate magnetic field exposure and was used only in North American studies [29]. However, we used wire codes because our aim was to assess the role of selection bias and this approach could be applied to any known address without requiring active participation or property access.…”
Section: Discussionmentioning
confidence: 99%
“…In one clever paper in which the pros and cons of the association between EMFs and childhood brain cancer were debated by two teams, each composed of eight international experts, using 12 pre-determined questions, arguments on both sides ultimately concluded that further research is necessary, an opinion vigorously championed by Carpenter in his paper Electromagnetic fields and cancer: the cost of doing nothing [10]. However, contributing to the confusion regarding EMF exposure are a number of methodological issues pertaining to the measurement of EMF, both in and around residences and in the workplace, issues that have sparked almost as much debate and research as the question of EMF exposure's role in disease [143], [148]- [154]. Such issues include questions about the accuracy of EMF measurements, how to avoid bias in subject selection, where best to measure EMF exposure (e.g., a child's bedroom versus elsewhere in or around the home), how to deal international variations in wiring techniques, how to interpret changes in electrical wiring over time and their effects, and how to adjust for the myriad of other potential confounders like other household exposures and exposures, EMF and otherwise, outside of the home.…”
Section: Electromagnetic Fieldsmentioning
confidence: 99%